A Morphological and Immunohistochemical Study of the Tumoral and Inflammatory Cells in Pancreatic Ductal Adenocarcinoma - Vlad Herlea; Elena Stoica Mustafa; Andreea Cristina Iorgescu; Nicolae Catalin Pechianu; Dragos Cretoiu; Maria Sajin; Simona Olimpia Dima; Catalin Vasilescu; Cezar Stroescu; Constantin Ungureanu; Traian Dumitrascu; Vladislav Brasoveanu; et al. (Journal of Immunology Research)
This study is aimed at investigating tumoral and inflammatory cells and the significance of the prognostic factors of pancreatic ductal adenocarcinoma (PDAC); it is also aimed at determining the role of immunohistochemistry in the diagnosis and prognosis of this neoplasm. Materials and Methods. 230 cases of pancreatic ductal adenocarcinoma were included in the study group; these cases were selected from the archives of the Department of Pathology of the Fundeni Clinical Institute over a ten-year period. Immunohistochemistry was performed using the following antibodies: MUC 1, CD 34, Factor VIII, CD 68, MMP-7, CEA, p21, p53, and Ki 67. Results. There were 133 male (57.8%) and 97 female (42.2%) patients included in this study, with ages between 20 and 81 years old (mean age: 58.2 years) and with tumors located in the pancreatic head (n=196; 85.2%), pancreatic body (n=12; 5.2%), and pancreatic tail (n=20, 8.7%), as well as panpancreatic tumors (n=2; 0.9%). Patients presented with early stages (IA and IB), with low pathologic grade (G1), with small size tumors (less than 1-1.5 cm), with tumors located in the head of the pancreas, (p53: negative; p21: positive; and CD 68: positive in peritumoral tissue), with low nuclear index (Ki 67<10%), without metastases at the time of surgery (had a better prognosis), and with a survival rate of about 7 months. Conclusions. Immunohistochemistry is useful for an accurate diagnosis, differential diagnosis, and establishment of additional factors that might have a prognostic importance. It is recommended to study peritumoral tissue from the quantitative and qualitative points of view to increase the number of prognostic factors. This study represents a multidisciplinary approach, and it is a result of teamwork; it presents histopathological methods of examination of this severe illness and describes only a part of the scientific effort to determine the main pathological mechanisms of this neoplasm.